ENGLISH EXTRACURRICULAR AND ITS ROLE TO IMPROVE STUDENTS’ ENGLISH SPEAKING ABILITY - Muhammad Yuseano Kardiansyah; Laila Ulsi Qodriani (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2018)
This research investigates both inside and outside of classroom activities to reveal the influence of English extracurricular in improving students’ English speaking ability in tertiary level. It is a response toward imbalance English speaking ability among students in English speaking classes reflected by their learning achievement. Students who belong to English extracurricular are indicated to have more significant progress to their English speaking ability compare to others who do not. Therefore, an attempt to explore further this phenomenon is necessary to do. The object of this research is all conversation classes for students from batch 2015 on academic year 2016/2017 at English department of Universitas Teknokrat Indonesia, in which some of them are the members of Teknokrat English Club as one of extracurricular activities in that university. In accordance, the researchers apply both qualitative and quantitative method in processing all data to gain comprehensive result of investigation. The data are gained by doing field observation and students’ learning achievement evaluation. While the objectives of this research are (a) assisting to solve problem and find out alternative to improve students’ ability communicating in English and (b) providing knowledge about the role of English extracurricular in supporting students to achieve the competence of English speaking ability in conversation class.